2016
DOI: 10.1016/j.biomaterials.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cell-secreted matrices perpetuate the bone-forming phenotype of differentiated mesenchymal stem cells

Abstract: Prior to transplantation, mesenchymal stem/stromal cells (MSCs) can be induced toward the osteoblastic phenotype using a cocktail of soluble supplements. However, there is little evidence of differentiated MSCs directly participating in bone formation, suggesting that MSCs may either die or revert in phenotype upon transplantation. Cell-secreted decellularized extracellular matrices (DMs) are a promising platform to confer bioactivity and direct cell fate through the presentation of a complex and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 44 publications
(74 reference statements)
2
99
2
Order By: Relevance
“…For in vivo studies, MSCs genetically modified to express firefly luciferase (UC Davis Center of Excellence in Gene Therapy) were expanded in α-MEM and used at passages 9–10. [10] Culture media was refreshed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vivo studies, MSCs genetically modified to express firefly luciferase (UC Davis Center of Excellence in Gene Therapy) were expanded in α-MEM and used at passages 9–10. [10] Culture media was refreshed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…[3] MSCs are multipotent cells that, among other phenotypes, can participate in bone formation directly by differentiating toward the osteoblastic phenotype [46] or indirectly by secreting paracrine acting trophic factors that stimulate angiogenesis and regulate local inflammation. [710] Regardless of their contribution, long-term survival and engraftment of MSCs to defect sites is poor, [11, 12] drastically decreasing the therapeutic potential of MSC-based treatments. Strategies that boost cell retention will likely translate into greater functional benefit, motivating the need for improved methods to retain cells at the defect site while promoting their survival and function to achieve the desired clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the MSC spheroids adjusted their packing density to allow for the transport of oxygen and nutrients, this came at the expense of ECM deposition and available integrin sites for cell adhesion. Cellderived matrix enhances cell survival and function [53,54], and MSC spheroid formation can enhance the production of ECM proteins such as laminin, elastin, type 1 collagen and fibronectin [31,55,56]. Furthermore, we recently demonstrated that MSC spheroids containing 15 000 cells per spheroid deposit a collagen-rich ECM, and that the MSCs' integrin-ECM interactions drive cell fate [57].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, allografts, xenografts, or artificial bone substitutes may expose the patient to severe risks of foreign body reactions and infections (5). Stem cells represent the new frontier in the field of regenerative medicine and are seen as a promising and suitable means to overcome the aforementioned drawbacks (6)(7)(8). Numerous studies report that adult stem cells can be isolated from several organs and tissues.…”
Section: Introductionmentioning
confidence: 99%